Developmental Angiogenesis Requires the Mitochondrial Phenylalanyl-tRNA Synthetase - Li, Bowen; Chen, Kun; Liu, Fangfang; Zhang, Juan; Chen, Xihui; Chen, Tangdong; Chen, Qi; Yao, Yan; Hu, Weihong; Wang, Li; Wu, Yuanming (Frontiers in Cardiovascular Medicine, 2021)
Background: Mitochondrial aminoacyl-tRNA synthetases (mtARSs) catalyze the binding of specific amino acids to their cognate tRNAs and play an essential role in the synthesis of proteins encoded by mitochondrial DNA. Defects in mtARSs have been linked to human diseases, but their tissue-specific pathophysiology remains elusive. Here, we examined the role of mitochondrial phenylalanyl-tRNA synthetase (FARS2) in developmental angiogenesis and its potential contribution to the pathogenesis of cardiovascular disease. Methods: Morpholinos were injected into fertilized zebrafish ova to establish an in vivo fars2 knock-down model. Visualization of the vasculature was achieved by using Tg (fli1: EGFP) y1 transgenic zebrafish. In addition, small interference RNAs (siRNAs) were transferred into human umbilical vein endothelial cells (HUVECs) to establish an in vitro FARS2 knock-down model. Cell motility, proliferation, and tubulogenesis were determined using scratch-wound CCK8, transwell-based migration, and tube formation assays. In addition, mitochondria- and non-mitochondria-related respiration were evaluated using a Seahorse XF24 analyzer and flow cytometry assays. The expression levels of transcripts and proteins were performed using qRT-PCR and western blotting, respectively. Results: Knock-down of fars2 hampered embryonic development in zebrafish and delayed formation of the vasculature in Tg (fli1: EGFP) y1 transgenic zebrafish. In addition, siRNA-mediated knock-down of FARS2 impaired angiogenesis in HUVECs, as indicated by decreased cell motility and tube formation capacity. Knock-down of FARS2 also produced variable decreases in mitochondrial- and non-mitochondrial respiration in HUVECs, and disrupted the regulatory pathways of angiogenesis in both HUVECs and zebrafish. Conclusion: Our current work offers novel insights into angiogenesis defects and cardiovascular diseases induced by FARS2 deficiency.